Educação ambiental e educação do campo na produção de novas racionalidades : diante da cultura globalizada - Ferreira, Sebastião (2010)
This piece of work aimed to comprehend the socio-environmental phenomena – the Environmental Education developed by the Agricultural Family’s School from Jaguaré, Jaguaré-ES – had as its purpose to search the Environmental Education’s articulation with the Country’s Education in the production of new rationalities. The socio-environmental experiences and the space-time teaching with community environmental practices, turns out to be consisted in a learning community, in a movement of belonging in the knowledge and doings. It is a qualitative research, with a phenomenological and hermeneutic influence as it is aimed to comprehend and interpret the phenomena which show by themselves – in the reported and lived experiences – relying on the complexity and transdisciplinarity. The surveyed data were derived from semi-structured interviews with monitors, students and peasant families, with records of photographs and audio recording; and from a living experience in the community environment, with a record of photographs and Field Journal. From the understanding and interpretation of reality studied, it is noticed that the School holds a training work with the students and their families, following its Training Plan, with all orientation focused on agro ecology. Within the family and community socio-environmental reality, the changes are manifested in a shy way, the students and their families have the understanding of the problems that the economist and immediate rationality causes to the environment, as well as social and environmental consequences. It is also noted that the urban and selfish vision, which is due to the hegemonic paradigm of modern science, hovers in these spaces and interferes in family and community social organizations, at the same time realize the need to take the training, recognize the experience and break with the hegemonic paradigm of modern science